Analysis of Gibran Rakabuming Raka's Personal Branding Strategy as a Leader Through the Tiktok Application: Analisis Strategi Personal Branding Gibran Rakabuming Raka Sebagai Pemimpin Melalui Aplikasi Tiktok - Ridwan, Elent Praditya; Syafira, Aulia Firda; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
Using Henri Tajfel and John Turner's Social Identity Theory, this study examines Gibran Rakabuming Raka's personal branding approach on the TikTok platform Through a descriptive qualitative approach, the research explores how Gibran builds an online identity, manages a diverse audience, and overcomes privacy risks on social media. Through innovative and engaging TikTok content, Gibran was able to establish his own brand as a youthful leader who is up to date, relatable to the younger generation, and responsive, according to the findings. With more than 4.8 million followers, Gibran is able to create emotional closeness and build positive public perceptions of his leadership.